Multimodal fake news detection using text and image - Biswas, Trisha; Lamia, Tasmim Afroj; Shykat, Tarikul Islam; Rafi, Md. Arifin Ahmed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.